2009
DOI: 10.1063/1.3077210
|View full text |Cite
|
Sign up to set email alerts
|

Shape control of FePt nanocrystals

Abstract: FePt nanocrystals were prepared by simultaneous reduction of platinum acetylacetonate and thermal decomposition of iron pentacarbonyl in properly chosen solvents/surfactants. A variety of FePt nanocrystals, including nanowires, nanorods, nanocubes, and nanosized multipods, were successfully obtained. The shape control was realized by simply varying synthesis parameters. The as-synthesized nanocrystals, having chemically disordered fcc structure, are found to be superparamagnetic at room temperature and their f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 20 publications
(30 reference statements)
0
22
0
Order By: Relevance
“…101,103,[125][126][127][128][129][130][131][132] These alloy nanoparticles are now routinely prepared either by decomposition/ reduction of metal carbonyls and metal salts, or by coreduction of two metal salts. 101,103,[125][126][127][128][129][130][131][132] These alloy nanoparticles are now routinely prepared either by decomposition/ reduction of metal carbonyls and metal salts, or by coreduction of two metal salts.…”
Section: View Article Onlinementioning
confidence: 99%
“…101,103,[125][126][127][128][129][130][131][132] These alloy nanoparticles are now routinely prepared either by decomposition/ reduction of metal carbonyls and metal salts, or by coreduction of two metal salts. 101,103,[125][126][127][128][129][130][131][132] These alloy nanoparticles are now routinely prepared either by decomposition/ reduction of metal carbonyls and metal salts, or by coreduction of two metal salts.…”
Section: View Article Onlinementioning
confidence: 99%
“…Many experimental and theoretical results have been published related to the magnetic properties of thin films some of which are composed of binary mixture of nanocrystals. Such mixtures can have pronounced effects of phase separation like kinetics especially in weak magnetic fields.…”
Section: Resultsmentioning
confidence: 99%
“…The composition of the nanoparticles in stage 1 was Fe 35 Pt 65 , indicating that the number of Pt atoms was evidently higher than that of the Fe atoms. The result suggested that the reduction of Pt salt was faster than the decomposition of Fe(CO) 5 in solutions, resulting in more Pt atoms entering into the embryo in the nucleation process [15]. In stage 2, the composition of the FePt NPs was determined to be Fe 38 Pt 62 , in which the content of Fe atoms was slightly increased due to the accelerated decomposition of the Fe salt.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the self-assembled arrays had a cubic packing. The shape control of the FePt NPs was also studied by Liu and Chen [15,16], in which the surfactants were found to play a crucial role in controlling the shape of the nanoparticles. Though the shape-anisotropic FePt nanoparticles were reported by a few literatures, the detailed growth behaviors involving the formation of the nanoparticles are not fully understood.…”
Section: Introductionmentioning
confidence: 99%